The online activism of mock translanguaging: Language style, celebrity persona, and social class in China. (June 2022) - Gao, Shuang
Abstract: This paper examines a viral language style that emerged during online activism against a Chinese celebrity after she was announced the winner of an architecture award. Drawing upon insights from celebrity studies, online activism, and social semiotics, I examine how netizens creatively appropriate and mock celebrity language, focusing on the semiotic work netizens engage in to mobilize emotions, form solidarity networks, and perform collective action as they reveal the moral failures, injustice, and falsehood of celebrity culture. Three semiotic strategies are found to be key in enabling netizens to formulate their critique: entextualization, stylization, and typification. In this process, language serves multiple functions: it is the target of critique, a proxy for discussing social issues, a tool for building solidarity through mutual learning, and a creative way of pursuing fun. I argue that these semiotic moves turn language into power, allowing netizens to articulate discontent against the rich amid increasing disparity and lack of trust in a neoliberal society.